Imagery in Poetry: An Assessment of Poems in Compulsory English Course of Class Eleven in Nepal (Kaumodaki: Journal of Multidisciplinary Studies, 2022)
This study aims to analyze poetic imagery applied in the poems prescribed in compulsory English course of class eleven in Nepal. Feeling and emotions in poetry are mostly expressed through imagery. Based on primary and secondary data, this paper first critically generalizes definition of imagery and its types and makes discussions on all prescribed poems. It is found that most common images in the poems are visual, auditory, tactile and kinesthetic. Olfactory and gustatory images are less realized in the poems. Most dominant imagery in all poems is visual. Most of the poet have used this imagery to condition things in a context and to communicate desired message effectively. The analysis asserts that understanding imagery and its types would certainly help students perceive ideas in poems and analyze them critically.